Negative thermal expansion material, manufacturing method of negative thermal expansion material, negative thermal expansion material fine particles, actuator material, actuator element, composite material, and component
Patent Information
- Application Number
- JP2023121781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
【0018】 本開示によれば、負熱膨張を示す新たな材料を提供できる。
Smart Images

Figure 2025018241000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative thermal expansion material, a method for producing a negative thermal expansion material, a group of negative thermal expansion material particles, an actuator material, an actuator element, a composite material, and a part. [Background technology]
[0002] It is generally known that materials expand with increasing temperature. However, the recent high level of development in industrial technology requires that even the thermal expansion, which is the fate of solid materials, be controlled. -5 ), which is considered to be a small change in shape by ordinary standards, is a major problem in fields such as semiconductor device manufacturing, which requires high precision at the nanometer level, and precision equipment, where even the slightest distortion of a part can have a significant effect on its function. In addition, in devices that combine multiple materials, differences in the thermal expansion of the constituent materials can cause other problems such as interface peeling and disconnection.
[0003] On the other hand, negative thermal expansion materials are also known, whose lattice volume decreases with increasing temperature (having a negative thermal expansion coefficient). For example, β-Cu, which has a monoclinic crystal structure, is one material that exhibits large negative thermal expansion over a wide temperature range. 1.8 Zinc 0.2 V 2 O 7 is known (see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-210198 A Summary of the Invention [Problem to be solved by the invention]
[0005] In order to utilize negative thermal expansion materials for various applications, it is desirable to develop new materials that are excellent not only in negative thermal expansion characteristics but also in at least one of electrical characteristics, physical characteristics, cost of the materials included, availability, environmental impact, etc.
[0006] The present disclosure has been made in view of such circumstances, and one of its purposes is to provide a new material exhibiting negative thermal expansion.
Means for Solving the Problems
[0007] In order to solve the above problems, the negative thermal expansion material according to an aspect of the present disclosure has a general formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, W, and satisfies 0 < x < 2, 0 ≦ y < 2, 0 ≦ z ≦ 2.) and contains an oxide represented by the formula.
[0008] Another aspect of the present disclosure is a negative thermal expansion material. This negative thermal expansion material takes any one of the crystal systems that Cu 2 V 2 O 7 or Cu 2 P 2 O 7 can take, and at least a part of Cu in Cu 2 V 2 O 7 or Cu 2 P 2 O 7 is substituted with Ca, and at least a part of the remaining Cu, V, and P is substituted with other elements or not substituted, and contains a compound.
[0009] Another aspect of the present disclosure is a method for manufacturing a negative thermal expansion material. This method has a general formula (1) Cu 2-x-y Cax R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, W, and satisfies 0 < x < 2, 0 ≤ y < 2, 0 ≤ z ≤ 2.) A compound represented by the general formula (1) is produced from an aqueous solution containing a raw material of the compound and an acid.
[0010] Still another aspect of the present disclosure is a method for producing a negative thermal expansion material. This method involves Cu 2 V 2 O 7 or Cu 2 P 2 O 7 taking any crystal system among the possible crystal systems, and producing the above compound from an aqueous solution containing a raw material of a compound in which at least a part of Cu in Cu 2 V 2 O 7 or Cu 2 P 2 O 7 is substituted with Ca, and at least a part of any of the remaining Cu, V, and P may be substituted with other elements or not substituted, and an acid.
[0011] Still another aspect of the present disclosure is a group of negative thermal expansion micro material particles. This group of negative thermal expansion micro material particles has the general formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7(R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, W, and satisfies 0 < x < 2, 0 ≤ y < 2, 0 ≤ z ≤ 2.) It contains an oxide represented by, and is composed of fine particles having a volume frequency median particle diameter (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering particle size distribution analyzer.
[0012] Yet another aspect of the present disclosure is a group of negative thermal expansion micro-material particles. This group of negative thermal expansion micro-material particles is Cu 2 V 2 O 7 or Cu 2 P 2 O 7 takes any of the crystal systems that can be taken, and at least a part of Cu in Cu 2 V 2 O 7 or Cu 2 P 2 O 7 is substituted with Ca, and at least a part of the remaining Cu, V, and P is substituted with other elements or not substituted, and is composed of fine particles having a volume frequency median particle diameter (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering particle size distribution analyzer.
[0013] Yet another aspect of the present disclosure is an actuator material. This actuator material has the general formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, W, and satisfies 0 < x < 2, 0 ≤ y < 2, 0 ≤ z ≤ 2.) It contains an oxide represented by.
[0014] Yet another aspect of the present disclosure is an actuator material. The actuator material comprises Cu 2 V 2 O 7 or Cu 2 P 2 O 7 The crystal system is one of the possible crystal systems of Cu. 2 V 2 O 7 or Cu 2 P 2 O 7 At least a portion of the Cu is replaced by Ca, and at least a portion of the remaining Cu, V and P is replaced by other elements or not replaced.
[0015] Yet another aspect of the present disclosure is an actuator element, the actuator element including the actuator material described above.
[0016] Yet another aspect of the present disclosure is a composite material comprising a positive thermal expansion material having a positive linear expansion coefficient, and at least one of the negative thermal expansion material and the negative thermal expansion material fine particles.
[0017] Yet another aspect of the present disclosure is a part, the part including the composite material described above. Effect of the Invention
[0018] According to the present disclosure, a new material exhibiting negative thermal expansion can be provided. [Brief description of the drawings]
[0019] [Figure 1] 1 is a diagram illustrating an actuator element according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a diagram showing X-ray diffraction patterns of the negative thermal expansion material of Example 1 (upper row) and the comparative example (lower row). [Diagram 3] FIG. 2 is a diagram showing the electrical resistivity of the negative thermal expansion material of Example 1 and the negative thermal expansion material of the comparative example. [Figure 4]FIG. 2 is a diagram showing the linear thermal expansion of the negative thermal expansion material of Example 1. [Diagram 5] FIG. 1 is a diagram showing the linear thermal expansion of an epoxy resin alone, a composite material in which the negative thermal expansion material of Example 1 is mixed with an epoxy resin at a volume ratio of 30%, and a composite material in which the negative thermal expansion material of the comparative example is mixed with an epoxy resin at a volume ratio of 30%. [Figure 6] FIG. 2 is a diagram showing the measurement results of electric field-induced strain of the negative thermal expansion material of Example 1. [Figure 7] FIG. 4 is a diagram showing the relationship between voltage and linear strain of the negative thermal expansion material of Example 1. [Figure 8] FIG. 1 shows X-ray diffraction patterns of the negative thermal expansion material of Example 2 (upper row) and the comparative example (lower row). [Figure 9] FIG. 13 is a diagram showing the particle size distribution of the negative thermal expansion material of Example 3. [Figure 10] FIG. 13 is a diagram showing the linear thermal expansion of a simple epoxy resin and a composite material in which the negative thermal expansion material of Example 3 is mixed into the epoxy resin in an amount of 30% by volume. [Figure 11] FIG. 1 shows X-ray diffraction patterns of the negative thermal expansion material of Example 4 (upper row) and the comparative example (lower row). [Figure 12] FIG. 1 shows X-ray diffraction patterns of the negative thermal expansion material of Example 5 (upper row) and the comparative example (lower row). [Figure 13] FIG. 13 is a diagram showing the measurement results of electric field-induced strain of the negative thermal expansion material of Example 6. [Figure 14] FIG. 1 shows the results of measuring the linear thermal expansion of Cu2V2O7 with various element substitutions. [Figure 15] FIG. 1 shows the results of measuring the electrical resistivity of Cu2V2O7 with various element substitutions. [Figure 16] FIG. 1 shows a possible crystal system for Cu1.8Zn0.2V2-zPzO7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] [Negative thermal expansion materials] The inventors have selected Cu as a candidate material that exhibits negative thermal expansion. 2 V2 O 7 The crystal structure of the α-Cu alloy is rectangular. 2 V 2 O 7 is attracting attention as a multiferroic material in which ferroelectricity and weak paramagnetism coexist, and in a relatively wide temperature range including room temperature and above, it exhibits anisotropic thermal deformation of the crystal lattice, which is thought to be due to structural instability. As a result, negative thermal expansion appears, in which the unit cell volume shrinks with increasing temperature, over a wide temperature range.
[0021] Cu 2 V 2 O 7 Cu can have at least three phases: the orthorhombic α phase, the monoclinic β phase, and the triclinic γ phase (see, for example, S. Bhowal et al., Phys. Rev. B 95, 075110 (2017)). 2 V 2 O 7 Closely related to Cu 2 P 2 O 7 can take the monoclinic α phase or the monoclinic β phase (see, for example, NK Shi et al., J. Am. Chem. Soc. 142, 3088 (2020)). 2 V 2 O 7 Substitution of some of the Cu and V sites with other elements, or Cu 2 P 2 O 7 When some of the Cu sites or P sites are replaced with other elements, the conventional α-Cu 2 V 2 O 7 We have discovered that negative thermal expansion properties can be realized that are not possible with conventional materials, and have devised the negative thermal expansion materials shown below. 2 V 2 O 7 or Cu 2 P 2 O 7 When such element substitution is performed on Cu, the crystal system is 2 V 2 O 7 or Cu 2 P2 O 7 It can be reasonably predicted that the crystal system will be one of the possible crystal systems of Cu. 1.8 Zinc 0.2 V 2-z P z O 7 Depending on the value of z and the temperature, 2 V 2 O 7 , α-Cu 2 P 2 O 7 , β-Cu 2 P 2 O 7 It has been shown by the present inventors that this has the same crystal system as that of
[0022] The negative thermal expansion material disclosed herein is Cu 2 V 2 O 7 or Cu 2 P 2 O 7 The crystal system is one of the possible crystal systems of Cu. 2 V 2 O 7 or Cu 2 P 2 O 7 The element replacing any of Cu, V, and P includes a compound in which at least a part of the Cu is replaced by Ca, and at least a part of any of the remaining Cu, V, and P is replaced by another element or is not replaced. 2 V 2 O 7 or Cu 2 P 2 O 7Any element can be used as long as it can form one of the possible crystal systems. For example, an element with an atomic radius or ionic radius similar to any of Cu, V, and P may be used. From this perspective, elements that can substitute for Cu may include Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, etc. Also, elements that can substitute for V may include Al, Si, P, S, Ge, Zr, Mo, Sn, W, etc. Elements that can substitute for P may include Al, Si, S, V, Ge, Zr, Mo, Sn, W, etc.
[0023] The negative thermal expansion material of the present disclosure has the general formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, W, and satisfies 0 < x < 2, 0 ≤ y < 2, 0 ≤ z ≤ 2.) and contains an oxide represented by the formula.
[0024] According to this aspect, by substituting Cu with Ca, which is widely present in nature, inexpensive, and easily available, a new negative thermal expansion material that is more inexpensive and has a smaller environmental impact can be provided.
[0025] The negative thermal expansion material of the present disclosure may have negative thermal expansion characteristics in all or at least a part of the temperature range of 100K to 500K, 200K to 380K, or 300K to 500K. The at least a part of the temperature range may be any temperature width, for example, it may be 1K or 100K. The negative thermal expansion material of the present disclosure may not have negative thermal expansion characteristics in a part of the above temperature range.
[0026] The thermal expansion coefficient α of the sintered body of the negative thermal expansion material of the present disclosure may be α = -3.5 ppm / K or less, more preferably α = -5 ppm / K or less, even more preferably α = -10 ppm / K or less, even more preferably -15 ppm / K or less, and most preferably -30 ppm / K or less in all or at least a part of the temperature range of 100K to 500K, 200K to 380K, or 300K to 500K. The thermal expansion coefficient α of the sintered body of the negative thermal expansion material of the present disclosure may be -1 ppm / K or less, -2 ppm / K or less, -3 ppm / K or less, -4 ppm / K or less, -6 ppm / K or less, -7 ppm / K or less, -8 ppm / K or less, -9 ppm / K or less, -20 ppm / K or less, -25 ppm / K or less, -35 ppm / K or less, -40 ppm / K or less in all or at least a part of the above temperature range. The thermal expansion coefficient α in a certain temperature range may be the average value of the thermal expansion coefficients measured at a plurality of temperatures included in the temperature range, or may be the average value of the thermal expansion coefficients measured at the lowest and highest temperatures in the temperature range. The thermal expansion coefficient α at a certain temperature is expressed as the rate of change of the linear thermal expansion ΔL / L or the bulk thermal expansion ΔV / V measured near that temperature. The linear thermal expansion ΔL / L or the bulk thermal expansion ΔV / V may be measured at temperature intervals of, for example, 1K, 2K, 5K, 10K, etc., depending on the measurement environment, measurement device, etc.
[0027] The thermal expansion coefficient α of the sintered body of the negative thermal expansion material of the present disclosure may have a linear expansion coefficient of, for example, α = -3.5 ppm / K or less, more preferably α = -5 ppm / K or less, even more preferably α = -10 ppm / K or less, even more preferably -15 ppm / K or less, and most preferably -30 ppm / K or less at 100K, 150K, 200K, 250K, 300K, 350K, 400K, 450K, 500K, particularly 300K. The thermal expansion coefficient α of the sintered body of the negative thermal expansion material of the present disclosure may be, at the above temperatures, −1 ppm / K or less, −2 ppm / K or less, −3 ppm / K or less, −4 ppm / K or less, −6 ppm / K or less, −7 ppm / K or less, −8 ppm / K or less, −9 ppm / K or less, −20 ppm / K or less, −25 ppm / K or less, −35 ppm / K or less, or −40 ppm / K or less.
[0028] The electrical resistivity of the negative thermal expansion material of the present disclosure is 2×10 3 The electrical resistivity of the negative thermal expansion material of the present disclosure may be 1×10 [Ω·cm] or more in all or at least a portion of the temperature range of 350 K or less. 4 The electrical resistivity of the negative thermal expansion material of the present disclosure may be 1×10 [Ω·cm] or more over all or at least a portion of the temperature range of 280 K or less. 5 This allows the negative thermal expansion material of the present disclosure to be suitably used in applications requiring insulation, such as sealing materials for electronic devices and circuit boards.
[0029] The negative thermal expansion material of the present disclosure may have electrostrictive properties that change shape upon application of an electric field in all or at least a part of the temperature range of 100 K to 500 K, 200 K to 380 K, or 300 K to 500 K. This makes it possible to suitably use the negative thermal expansion material of the present disclosure in a new element having an actuator function induced by application of an electric field.
[0030] The lower limit of x may be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, or 1.9. The upper limit of x may be 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or 0.1.
[0031] The lower limit of y may be 0, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, or 1.9. The upper limit of y may be 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or 0.1.
[0032] The lower limit of z may be 0, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9. The upper limit of z may be 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1. When z=2, A=P may be satisfied. The range of values of z may be 0≦z<2.
[0033] [Method of manufacturing negative thermal expansion material] The method for producing a negative thermal expansion material of the present disclosure may include a step of producing the compound of the above general formula (1) using an aqueous solution containing raw materials of the compound represented by the above general formula (1) and an acid. By utilizing the form of an aqueous solution that is easy to handle at low temperatures, the negative thermal expansion material can be produced relatively inexpensively. The step of producing the compound of the general formula (1) may include a step of producing a powder of the compound of the general formula (1).
[0034] The above-mentioned production method may include a step of granulating the compound represented by the general formula (1) by a spray-drying method using an aqueous solution to produce a powder of the salt of the compound represented by the general formula (1). The above-mentioned production method may also include a step of granulating the compound represented by the general formula (1) by a freeze-drying method using an aqueous solution to produce a powder of the salt of the compound represented by the general formula (1). This makes it possible to produce a powder of the salt of the negative thermal expansion material without requiring excessive energy or expensive equipment for granulation or pulverization at high temperatures.
[0035] The above-mentioned production method may include a step of heating the salt powder to decompose the acid, and a step of firing the powder from which the acid has been decomposed to produce an oxide sintered body. This makes it possible to produce an oxide sintered body of a desired shape with relatively low energy.
[0036] The above-mentioned manufacturing method may include the step of adding polyethylene glycol to the aqueous solution to form a gel, which allows for the formation of finer crystal grains.
[0037] The above-mentioned manufacturing method may include a step of heating the gel to decompose the acid, and a step of sintering the powder produced by decomposing the acid in the gel to produce a sintered oxide body. This makes it possible to produce an oxide sintered body of a desired shape with relatively low energy.
[0038] The acid may be an organic acid or an inorganic acid. The organic acid may be citric acid, acetic acid, etc. The inorganic acid may be nitric acid, etc. It is preferable to use an acid that allows the compound raw material to be easily dispersed.
[0039] The method for producing a negative thermal expansion material of the present disclosure may include a step of producing a polycrystalline sintered body of the above general formula (1) by using a solid-phase reaction method.
[0040] [Negative thermal expansion material particles] The negative thermal expansion material fine particles of the present disclosure are represented by the above general formula (1) and are composed of fine particles having a volume frequency median diameter (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering type particle size distribution evaluation device. The upper limit of the median diameter is preferably 4 μm, more preferably 2 μm, and even more preferably 1 μm.
[0041] According to this embodiment, precise thermal expansion control of micro components or local regions at the 10 μm level is possible. In addition, when the negative thermal expansion material fine particles are dispersed in a base such as a resin, the negative thermal expansion material fine particles can be prevented from settling, so that homogeneous dispersion can be achieved. Furthermore, if the median diameter of the negative thermal expansion material fine particles is equal to or smaller than the wavelength of visible light (300 nm to 800 nm), the transmittance of visible light can be maintained even when the negative thermal expansion material fine particles are mixed with a transparent or semi-transparent material such as glass or acrylic.
[0042] Here, the term "fine particles" refers to an aggregate of smaller single crystal grains, and the term "fine particle group" refers to an aggregate of fine particles having a volume frequency median particle diameter (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering particle size distribution evaluation method. In the following, the "volume frequency median particle diameter (median diameter) as measured by a laser diffraction / scattering particle size distribution evaluation method" may simply be referred to as "particle diameter". The particle diameter of the fine particles can be appropriately changed by changing the conditions of the manufacturing method described below. For example, the particle diameter of the fine particles may be 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, 0.9 μm or less, 0.8 μm or less, 0.7 μm or less, 0.6 μm or less, 0.5 μm or less, 0.4 μm or less, 0.3 μm or less, 0.2 μm or less, or 0.1 μm or less.
[0043] The values of x, y, and z in general formula (1), the negative thermal expansion properties of the negative thermal expansion material fine particle group, the thermal expansion coefficient α, the electrical resistivity, the electrostriction properties, etc. may be the same as those of the above-mentioned negative thermal expansion material.
[0044] In the present disclosure, the linear expansion coefficient of the negative thermal expansion material fine particle group is evaluated as follows. It is technically difficult to measure the thermal expansion characteristics of a single particle, and if the thermal expansion characteristics of the sintered fine particles are measured, the negative thermal expansion material may be altered during the sintering process. Considering that the main use of negative thermal expansion materials is to combine them with materials such as resins and use them to suppress their thermal expansion, it is reasonable to evaluate the thermal expansion coefficient of the negative thermal expansion material fine particle group by measuring the degree to which thermal expansion is suppressed in a composite material in which the negative thermal expansion material fine particle group is combined with a general resin such as an epoxy resin. Therefore, in the present disclosure, the linear expansion coefficient of the negative thermal expansion material fine particle group is evaluated according to the composite rule, which predicts the linear expansion coefficient of the composite material by dividing the thermal expansion coefficient of each material by the volume ratio of the base material of the composite material and the negative thermal expansion material fine particle group dispersed in the base material.
[0045] The composite rule is that the volume ratio of the base and the linear expansion coefficient are ν m , α m , the volume ratio of the particles and the linear expansion coefficient are νf , α f , the linear expansion coefficient of the composite material is α c As, α c =ν m α m +ν f α f The linear thermal expansion of a composite material is predicted from the following equation. Here, ν m +ν f = 1. Based on this formula, α f =(α c -ν m α m ) / ν f The linear expansion coefficient of the negative thermal expansion material particles is evaluated by α f All of the above can be easily measured. By using this method, the linear expansion coefficient α of the negative thermal expansion material particles can be measured regardless of the type of base. f Since the same value can be obtained as m Any material can be used as the base material as long as its is known or measurable. However, when metal or ceramics is used as the base material, the heat treatment temperature for compounding is higher than that of resin, and the negative thermal expansion material may change during the compounding process, resulting in a value inferior to the negative thermal expansion that it should originally show. This has been reported in previous literature (e.g., "Matrix-filler interfaces and physical properties of metal matrix composites with negative thermal expansion manganese nitride", K. Takenaka, K. Kuzuoka, and N. Sugimoto, J. Appl. Phys. 118, 084902 (2015)). This is not preferable for the purpose of evaluating the linear expansion coefficient of negative thermal expansion material fine particle group. For this reason, it is preferable to use epoxy resin as the base material. For example, the α measured in a predetermined temperature range (e.g., 200K to 380K) using a composite material compounded with negative thermal expansion material fine particle group using epoxy resin as the base material is fThe average value of may be used as the linear expansion coefficient of the negative thermal expansion material fine particle group in that temperature range. Since the temperature range in which the negative thermal expansion material fine particle group shows a large negative thermal expansion may vary depending on the chemical composition, the temperature range in which the thermal expansion is evaluated may be changed as appropriate in order to properly evaluate the thermal expansion suppression ability of the negative thermal expansion material fine particle group. For example, 250K to 350K, 200K to 350K, 300K to 380K, etc. may be preferable. α at both ends of the temperature range f The average value of these may be used as the linear expansion coefficient of the negative thermal expansion material fine particles in that temperature range.
[0046] [Method of manufacturing negative thermal expansion material particles] The method for producing negative thermal expansion material fine particles of the present disclosure includes a step of spray-drying an aqueous solution containing at least one of a compound represented by general formula (1) and its raw material, and at least one of an acid, a salt, and an organometallic compound. The method may also include a step of pulverizing the obtained particles. The method may also include a step of classifying the obtained particles.
[0047] The pulverization process is carried out so as to obtain a negative thermal expansion micromaterial particle group consisting of fine particles having a volume frequency median particle size (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering particle size distribution evaluation device.
[0048] The spray drying method can obtain particles with smaller particle size, narrower particle size distribution, and isotropic particle shape compared to conventional solid-state reaction methods. This allows the powder to be pulverized with an overwhelmingly smaller mechanical load than when pulverizing large crystals obtained by conventional solid-state reaction methods, so that a group of fine particles that maintains the negative thermal expansion properties can be obtained. By incorporating a classification process such as sieving, the particle size and particle size distribution can be further adjusted.
[0049] The acid may be an organic acid or an inorganic acid. Examples of the organic acid that can be used include citric acid and acetic acid. The salt may be a salt of an organic acid and an alkali, or a salt of an inorganic acid and an alkali. Examples of the salt that can be used include metal nitrates, metal acetates, metal sulfates, metal chlorides, and metal fatty acids. Examples of the organometallic compounds that can be used include metal alkoxides and metal acetylacetonates. An aqueous solution in which a metal is dissolved in nitric acid, hydrochloric acid, sulfuric acid, or the like may be used.
[0050] When preparing the aqueous solution, the compound represented by general formula (1) itself may be dissolved, or a raw material for the compound represented by general formula (1) may be dissolved.
[0051] [Composite materials] The composite material of the present disclosure includes at least one of the negative thermal expansion material and the negative thermal expansion material fine particles of the present disclosure, and a positive thermal expansion material having a positive linear expansion coefficient, thereby providing a composite material that maintains the properties of the positive thermal expansion material while suppressing volumetric changes due to temperature changes.
[0052] The composite material may contain a negative thermal expansion material or a negative thermal expansion material fine particle group represented by the above-mentioned general formula (1) as the negative thermal expansion material or the negative thermal expansion material fine particle group. The composite material may contain a plurality of negative thermal expansion materials or negative thermal expansion material fine particle groups having different compositions selected from the negative thermal expansion material or the negative thermal expansion material fine particle group represented by the general formula (1). The composite material may further contain any type of negative thermal expansion material or negative thermal expansion material fine particle group other than the negative thermal expansion material represented by the general formula (1), such as Mn-Zn-Sn-N-based inverse perovskite-type manganese nitride and Mn-Zn-Ge-N-based inverse perovskite-type manganese nitride. The composite material may contain two or more types of negative thermal expansion materials or negative thermal expansion material fine particle groups.
[0053] The composite material may contain, as a positive thermal expansion material, a metal, a semiconductor, an insulator, a resin, a ceramic, etc. The composite material may contain only one of these positive thermal expansion materials, or may contain any combination of two or more of them.
[0054] The composite material may include at least one of a metal and a semiconductor as a positive thermal expansion material. The metal may include at least one of aluminum, copper, iron, titanium, and brass. The semiconductor may include, for example, silicon.
[0055] The composite material may include an insulator as a positive thermal expansion material, for example, the insulator may include at least one of glass, adhesive, pigment, and rubber.
[0056] The composite material may include a resin as a positive thermal expansion material, for example, at least one of an epoxy resin, a phenol resin, a fluororesin, an acrylic resin, an acrylonitrile butadiene resin, a polycarbonate, a polyimide, a polyamideimide, a polypropylene, a polyamide, a polyethylene, and a polyethylene terephthalate.
[0057] The composite material may include a ceramic as the positive thermal expansion material, for example, the ceramic may include at least one of silica, alumina, titania, zirconia, aluminum nitride, silicon nitride, and silicon carbide.
[0058] [Actuator] The actuator material of the present disclosure includes an oxide represented by the above general formula (1). The actuator element of the present disclosure includes an actuator material including an oxide represented by the above general formula (1). This makes it possible to realize a new element having an actuator function induced by application of an electric field.
[0059] The values of x, y, and z in the general formula (1), the negative thermal expansion characteristics of the actuator material, the thermal expansion coefficient α, the electrical resistivity, the electrostrictive characteristics, etc. may be the same as those of the negative thermal expansion material described above.
[0060] 1 is a diagram illustrating an actuator element according to an embodiment of the present invention, and FIG. 1 is a diagram illustrating an actuator element 10 according to an embodiment of the present invention. As shown in FIG.
[0061] The actuator section 12 includes the actuator material of the present disclosure described above. The actuator section 12 is made of the actuator material of the present disclosure and alumina (main component Al 2 O 3 ) may be included. The electrodes 14 and 16 are disposed so as to sandwich the actuator section 12. There are no particular limitations on the material of the electrodes 14 and 16, and any material may be used as long as it can apply a predetermined voltage to the actuator section 12.
[0062] An external power source (not shown) is electrically connected to the electrodes 14 and 16, for example, via wires or the like (not shown). A predetermined voltage is applied to the actuator section 12 via the electrodes 14 and 16. The application of the voltage can change the shape of the actuator section 12. The shape of the actuator element 10 is not particularly limited and can be appropriately selected depending on the purpose.
[0063] The actuator element of the present disclosure can be suitably used in precision positioning elements, various sensors, ultrasonic transmitters, micromachine driving parts, internal combustion engines, liquid ejection parts of inkjet printers, and the like.
[0064] [parts] The parts of the present disclosure include the above composite material, the above actuator material, the above actuator element, etc. This makes it possible to realize parts in which volume change with respect to temperature change is suppressed. Specifically, the parts can be suitably used in precision optical parts and machine parts, process equipment and tools, temperature compensation materials for fiber gratings, printed circuit boards, sealing materials for electronic parts, heat switches, refrigerator parts, artificial satellite parts, etc., which are sensitive to changes in shape and dimensions due to temperature. In particular, by making a composite material in which a negative thermal expansion material is dispersed in a matrix phase of a resin with a large positive thermal expansion coefficient, it becomes possible to suppress and control thermal expansion even in the resin material, making it possible to use it in various applications.
[0065] As described above, the negative thermal expansion material and negative thermal expansion material fine particles of the present disclosure have a relatively high electrical resistivity, and therefore composite materials, actuator materials, and actuator elements containing the negative thermal expansion material or negative thermal expansion material fine particles of the present disclosure are particularly suitable for use in parts requiring insulation.
[0066] [Example] By the method for producing the negative thermal expansion material disclosed herein, 1.9 Ca 0.1 V 2 O 7 (In the general formula (1), x = 0.1, y = 0, z = 0: Example 1), Cu 1.4 Ca 0.6 V 2 O 7 (In the general formula (1), x = 0.6, y = 0, z = 0: Example 2), Cu 1.6 Ca 0.4 V 2 O 7 (In the general formula (1), x = 0.4, y = 0, z = 0: Example 3), Cu 1.8 Ca 0.2 V 2 O 7 (In the general formula (1), x = 0.2, y = 0, z = 0: Example 4), Cu 1.8 Ca 0.1 Mg 0.1 V 2 O 7 (In the general formula (1), x=0.1, y=0.1, z=0, and R=Mg: Example 5), Cu1.8 Ca 0.2 V 1.8 P 0.2 O 7 A negative thermal expansion material of the following formula (1): x=0.2, y=0, z=0.2, A=P (Example 6) was produced.
[0067] Example 1 (Cu 1.9 Ca 0.1 V 2 O 7 ) negative thermal expansion materials are CuO, CaO, V 2 O 5 The raw materials were first weighed and mixed in a given molar ratio, then placed in an alumina crucible and fired in air at 500-700°C for 1-10 hours. The resulting calcined body was then crushed thoroughly in a mortar, placed in an alumina crucible, and heated in air at 550-800°C for 2-20 hours to obtain Cu. 1.9 Ca 0.1 V 2 O 7 For the second firing, the calcined body was pressed and molded before firing to obtain a sintered body.
[0068] Example 2 (Cu 1.4 Ca 0.6 V 2 O 7 ), Example 3 (Cu 1.6 Ca 0.4 V 2 O 7 ), and Example 4 (Cu 1.8 Ca 0.2 V 2 O 7 The negative thermal expansion material of was prepared by the spray-drying method. First, 1 g of the negative thermal expansion material obtained by the above solid-phase reaction method was added to 100 g of pure water together with 3 g of anhydrous citric acid, and stirred using a magnetic stirrer until all of the sample powder was dissolved. The sample to be dissolved in citric acid may be a fired material as in this example, or may be a raw material with a specified molar ratio.
[0069] The resulting aqueous solution was then dried and granulated using a spray dryer (ADL311: Yamato Scientific Co., Ltd.) to obtain a powder of citrate. This powder was placed in an alumina crucible and heated in air at 300 to 450°C for 1 to 6 hours to decompose the citric acid. The resulting powder was crushed thoroughly in a mortar, placed in an alumina crucible, and fired in air at 550 to 800°C for 2 to 10 hours using an electric furnace.
[0070] Example 5 (Cu 1.8 Ca 0.1 Mg 0.1 V 2 O 7 ) negative thermal expansion materials are CuO, CaO, MgO, V 2 O 5 was used as the raw material and obtained by the above-mentioned solid-state reaction method.
[0071] Example 6 (Cu 1.8 Ca 0.2 V 1.8 P 0.2 O 7 ) negative thermal expansion materials are CuO, CaO, V 2 O 5 , N.H. 4 H 2 PO 4 was used as the raw material and obtained by the above-mentioned solid-state reaction method.
[0072] FIG. 2 shows the Cu of Example 1. 1.9 Ca 0.1 V 2 O 7 (Top) and β-Cu for comparison 2 V 2 O 7 The lower part shows the X-ray diffraction pattern of Cu in the example. 1.9 Ca 0.1 V 2 O 7 β-Cu 2 V 2 O 7 It was shown to have the same crystal system as
[0073] FIG. 3 shows the Cu of Example 1. 1.9 Ca 0.1 V 2 O 7 and Cu as a comparative example1.8 Zinc 0.2 V 2 O 7 The electrical resistivity of the Cu in the example is shown. 1.9 Ca 0.1 V 2 O 7 is Cu in the comparative example 1.8 Zinc 0.2 V 2 O 7 It was shown that the electrical resistivity was higher than that of the Cu in Example 1. 1.9 Ca 0.1 V 2 O 7 The electrical resistivity of is about 10 at 250K. 6 [Ω cm], at 300 K it is about 10 5 [Ω cm], at 350K it is about 10 4 [Ω cm], at 400 K it is about 2×10 3 [Ω cm].
[0074] FIG. 4 shows the Cu of Example 1. 1.9 Ca 0.1 V 2 O 7 The linear thermal expansion coefficient α is the slope of the linear thermal expansion, i.e., the temperature derivative. In the case of an isotropic material with no directional dependency, the linear thermal expansion essentially represents the bulk thermal expansion, and there is a relationship of ΔV / V=3ΔL / L (V is the volume). In the case of Cu in Example 1, the linear thermal expansion coefficient α is α=3ΔL / L. 1.9 Ca 0.1 V 2 O 7 exhibited negative thermal expansion characteristics in the temperature range of 100 K to 500 K. The linear expansion coefficient α in the temperature range of 100 K to 300 K was -4.6 ppm / K, and the linear expansion coefficient α in the temperature range of 350 K to 500 K was -18.3 ppm / K.
[0075] FIG. 5 shows the results of the epoxy resin (Adeka EP-4100E / EH-105L) alone and the epoxy resin with Cu of Example 1. 1.9 Ca 0.1 V 2 O 7The composite material was mixed with 30% by volume of epoxy resin and Cu as a comparative example. 1.8 Zinc 0.2 V 2 O 7 The linear thermal expansion of the composite material is shown in Fig. 1. The positive thermal expansion material is epoxy resin, and the negative thermal expansion material is Cu of Example 1. 1.9 Ca 0.1 V 2 O 7 By adding Cu, the thermal expansion of the epoxy resin was suppressed in the temperature range of 100K to 400K. 1.9 Ca 0.1 V 2 O 7 In the temperature range of 100K to 400K, the Cu 1.8 Zinc 0.2 V 2 O 7 According to the evaluation method based on the above-mentioned rule of mixture, the linear expansion coefficient α of Example 1 and Comparative Example f The average values of from 250K to 350K were -28.4ppm / K and -38.0ppm / K, respectively.
[0076] FIG. 6 shows the Cu of Example 1. 1.9 Ca 0.1 V 2 O 7 The measurement results of the electric field induced strain are shown below. The electric field induced strain was measured at room temperature using the capacitance method. When a voltage was applied, a negative linear strain was obtained, which may be due to a phase transition. The insulating phase was maintained even when a voltage was applied, and electric field induced linear strain was obtained with little influence of Joule heat.
[0077] FIG. 7 shows the Cu of Example 1. 1.9 Ca 0.1 V 2 O 7 The relationship between the voltage and the linear strain is shown in Fig. 1. As the applied voltage increases, the amount of strain also increases. This shows that the amount of strain can be controlled by the electric field at room temperature.
[0078] FIG. 8 shows the Cu 1.4 Ca 0.6 V2 O 7 (Top) and β-Cu for comparison 2 V 2 O 7 The lower part shows the X-ray diffraction pattern of Cu in Example 2. 1.4 Ca 0.6 V 2 O 7 However, β-Cu 2 V 2 O 7 It was shown that the main component was
[0079] FIG. 9 shows the Cu of Example 3. 1.6 Ca 0.4 V 2 O 7 The particle size distribution of the volume frequency median particle size D 50 was shown to be less than 4 μm.
[0080] FIG. 10 shows the results of the epoxy resin (Adeka EP-4100E / EH-105L) alone and the epoxy resin with Cu of Example 3. 1.6 Ca 0.4 V 2 O 7 The linear thermal expansion of the composite material is shown in Fig. 1. The positive thermal expansion material is epoxy resin, and the negative thermal expansion material is Cu of Example 3. 1.6 Ca 0.4 V 2 O 7 By adding, the thermal expansion of the epoxy resin was suppressed in the temperature range of 100K to 400K. According to the evaluation method based on the above-mentioned rule of mixture, the linear expansion coefficient α f The average value of from 250K to 350K was -16.4ppm / K.
[0081] FIG. 11 shows the Cu of Example 4. 1.8 Ca 0.2 V 2 O 7 (Top) and β-Cu for comparison 2 V 2 O 7 The lower part shows the X-ray diffraction pattern of Cu in Example 4. 1.8 Ca 0.2 V 2 O 7β-Cu 2 V 2 O 7 It was shown to have the same crystal system as
[0082] FIG. 12 shows the Cu of Example 5. 1.8 Ca 0.1 Mg 0.1 V 2 O 7 (Top) and β-Cu for comparison 2 V 2 O 7 The lower part shows the X-ray diffraction pattern of Cu in Example 5. 1.8 Ca 0.1 Mg 0.1 V 2 O 7 β-Cu 2 V 2 O 7 It was shown to have the same crystal system as
[0083] FIG. 13 shows the Cu of Example 6. 1.8 Ca 0.2 V 1.8 P 0.2 O 7 The measurement results of the electric field induced strain are shown below. The electric field induced strain was measured at room temperature by the capacitance method. When a voltage was applied, a linear strain induced by the electric field was obtained.
[0084] In the examples, Cu is mainly used. 2 V 2 O 7 Although an example in which part of the Cu in the above is replaced with Ca has been described, it is believed that oxides in which part of the Cu is replaced with more or less Ca, or in which part of the Cu is further replaced with elements such as Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, and Bi, or in which part of the V is replaced with elements such as Al, Si, P, S, Ge, Zr, Mo, Sn, and W, will also exhibit similar negative thermal expansion properties.
[0085] Cu in α phase (rectangular crystal Fdd2) 2 V 2 O 7It is known that the crystal structure of Cu changes to the β phase (monoclinic C2 / c) by substituting a part of Cu with, for example, Zn, and that this phase exhibits a larger negative thermal expansion. 2+ (3d) 9 The orbital ordering produced by the electronic state of Cu 2+ An element with a different number of d electrons (in this case (3d) 10 Zn 2+ ) is substituted, causing the crystal to become distorted. The greater the distortion of the crystal caused by this element substitution, the greater the negative thermal expansion. 2 V 2 O 7 Cu(3d) in 9 It is essentially important to "disrupt the electronic configuration of Cu and introduce distortion into the crystal." 2 V 2 O 7 A part of Cu in 2+ It can be reasonably predicted that oxides in which elements with different numbers of d electrons, such as Ca, Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, and Bi, or oxides in which part of the V is replaced by elements such as Al, Si, P, S, Ge, Zr, Mo, Sn, and W, will exhibit similar negative thermal expansion properties through a similar mechanism.
[0086] Figure 14 shows Cu 2 V 2 O 7 The following shows the results of linear thermal expansion measurements of Cu with various element substitutions. 2 V 2 O 7 Compounds in which the Cu site or V site is replaced with various elements are also 2 V 2 O 7It has a negative thermal expansion property in the same manner. Therefore, it can be reasonably predicted that compounds obtained by variously changing the Ca composition ratio of the compounds of Example 1 and Example 3, or substituting a part of the Cu sites or V sites of the compounds of Example 1 and Example 3 with various elements and composition ratios also have a negative thermal expansion property in the same manner as the compounds of Example 1 and Example 3.
[0087] The negative thermal expansion material of the present disclosure has excellent properties such as high electrical resistivity and electrostriction characteristics by substituting a part of Cu with Ca. 2 V 2 O 7 It does not have. 2 V 2 O 7 It is not easy for those skilled in the art to conceive that such characteristics are exhibited by substituting a part of Cu in CuV₂O₆ with Ca. Since the manifestation of such characteristics is considered to be due to the substitution of a part of Cu with Ca, if a part of Cu is substituted with Ca (that is, if 0 < x < 2), oxides obtained by further substituting a part of Cu with elements such as Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, or substituting a part of V with elements such as Al, Si, P, S, Ge, Zr, Mo, Sn, W, etc. can be reasonably predicted to have the same electrical characteristics and electrostriction characteristics.
[0088] FIG. 15 shows the measurement results of the electrical resistivity of those obtained by performing various element substitutions on CuV₂O₆. The electrical resistivity of the compound of Example 1 is higher than that of any of the compounds shown in FIG. 15. Therefore, 2 V 2 O 7 It does not have. 2 V 2 O 7It is not something that a person skilled in the art would easily come up with, that a high electrical resistivity can be obtained by substituting part of the Cu sites of the compound of Example 1 with Ca. It can be reasonably predicted from general knowledge in material science that compounds in which the composition ratio of Ca in the compound of Example 1 is variously changed, or in which part of the Cu sites or V sites of the compound of Example 1 are further substituted with various elements and composition ratios, will have electrical properties similar to those of the compound of Example 1.
[0089] The present disclosure has been described above based on the embodiments. These embodiments are merely examples, and it will be understood by those skilled in the art that various modifications are possible in the combination of each component and each treatment process, and that such modifications are also within the scope of the present disclosure.
Claims
1. General formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, and Bi; A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, and W, and satisfies 0<x<2, 0≦y<2, and 0≦z≦2.) Negative thermal expansion material.
2. Cu 2 V 2 O 7 Or Cu 2 P 2 O 7 The crystal system is one of the possible crystal systems of Cu. 2 V 2 O 7 Or Cu 2 P 2 O 7 At least a part of Cu is replaced by Ca, and at least a part of the remaining Cu, V and P is replaced by other elements or not replaced. Negative thermal expansion material.
3. Has negative thermal expansion properties in at least a portion of the temperature range of 100K to 500K The negative thermal expansion material according to claim 1 or 2.
4. A linear expansion coefficient of -3.5 ppm / K or less in at least a part of the temperature range of 100 K to 500 K The negative thermal expansion material according to claim 1 or 2.
5. At 300K, it has a linear expansion coefficient of -3.5 ppm / K or less The negative thermal expansion material according to claim 1 or 2.
6. At least in a part of the temperature range from 250 K to 350 K, 5 The negative thermal expansion material according to claim 1 or 2, having an electrical resistivity of 1.0 [Ω·cm] or more.
7. Has electrostrictive properties in at least a portion of the temperature range of 100K to 500K The negative thermal expansion material according to claim 1 or 2.
8. The absolute value of linear strain is 200 ppm or more in at least a part of the temperature range of 100 K to 500 K. The negative thermal expansion material according to claim 1 or 2.
9. General formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, and Bi, and A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, and W, and satisfies 0<x<2, 0≦y<2, and 0≦z≦2), and an aqueous solution containing an acid is used to produce a compound represented by the general formula (1). Method for producing negative thermal expansion material.
10. Cu 2 V 2 O 7 Or Cu 2 P 2 O 7 The crystal system is one of the possible crystal systems of Cu. 2 V 2 O 7 Or Cu 2 P 2 O 7 The compound is produced from an aqueous solution containing an acid and a raw material of the compound in which at least a part of Cu is replaced by Ca and at least a part of any of the remaining Cu, V and P is replaced or not replaced by another element. Method for producing negative thermal expansion material.
11. General formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, and Bi, and A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, and W, and satisfies 0<x<2, 0≦y<2, and 0≦z≦2), and is composed of fine particles having a volume frequency median particle size (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering type particle size distribution evaluation device. Negative thermal expansion micromaterial particles.
12. Cu 2 V 2 O 7 Or Cu 2 P 2 O 7 The crystal system is one of the possible crystal systems of Cu. 2 V 2 O 7 Or Cu 2 P 2 O 7 At least a part of Cu is replaced by Ca, and at least a part of any of the remaining Cu, V and P is replaced or not replaced by other elements, and the compound is composed of fine particles having a volume frequency median particle size (median diameter) of 30 nm or more and less than 5 μm as measured by a laser diffraction / scattering type particle size distribution evaluation device. Negative thermal expansion micromaterial particles.
13. General formula (1) Cu 2-x-y Ca x R y V 2-z A z O 7 (R contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, and Bi; A contains at least one element selected from Al, Si, P, S, Ge, Zr, Mo, Sn, and W, and satisfies 0<x<2, 0≦y<2, and 0≦z≦2.) Actuator material.
14. Cu 2 V 2 O 7 Or Cu 2 P 2 O 7 The crystal system is one of the possible crystal systems of Cu. 2 V 2 O 7 Or Cu 2 P 2 O 7 At least a part of Cu is replaced by Ca, and at least a part of the remaining Cu, V and P is replaced by other elements or not replaced. Actuator material.
15. The actuator material according to claim 13 or 14 is included. Actuator element.
16. A positive thermal expansion material having a positive linear expansion coefficient; At least one of the negative thermal expansion material according to claim 1 and claim 2 and the negative thermal expansion material fine particle group according to claim 11 and claim 12; Includes Composite material.
17. The positive thermal expansion material includes at least one of a metal, a semiconductor, an insulator, a resin, and a ceramic.
17. The composite material of claim 16.
18. Comprising the composite material of claim 16 parts.
Citation Information
Patent Citations
Negative thermal expansion material and composite
JP2019210198A